Peran Akun Instagram @qalbcalligraphy dalam Pengembangan Mahārah al-Kitābah: Peran Akun Instagram @qalbcalligraphy dalam Mendukung Mahārah al-Kitābah - Syafiq Muhammad Qutub; Tatang; Yusuf Ali Tantowi; Ghazy Ahmad Filando (Language Development Center, 2026)
Background: Students’ illegible Arabic handwriting and minimal attention to calligraphy as a learning medium demand innovation in more effective visual learning media for supporting mahārah al-kitābah, adapting to the development of digital technology. Purpose: This study aims to describe the content characteristics and analyze the role of the Instagram account @qalbcalligraphy, as well as to reveal students’ responses regarding its use as a visual learning medium in supporting mahārah al-kitābah. Method: This study used a qualitative-descriptive approach with a case study design. Data collection techniques included observation, interviews, and documentation, involving eight ninth-grade male students at MTs Al-Ma’tuq selected through purposive sampling. The instruments used were observation sheets and interview guides. Data were analyzed interactively using the Miles, Huberman, and Saldana model. Results and Discussion: The findings of this study indicate that the Instagram account @qalbcalligraphy has strong visual characteristics that support mahārah al-kitābah. The calligraphy content uploaded by this account showcases neat, balanced Arabic writing techniques that adhere to writing rules, motivating students to improve their writing, so that students’ writing quality improved after viewing the content of the Instagram account @qalbcalligraphy. Students also responded positively to the use of the account, despite its limitations and challenges. Conclusions and Implications: The use of the Instagram account @qalbcalligraphy as a visual learning medium has the potential to support mahārah al-kitābah by providing educational Arabic calligraphy content and supplementary learning beyond the classroom, and can serve as an innovation for educators to utilize similar media in their learning. Future research is recommended to employ a quasi-experimental design with comparison groups and longer research periods, as well as compare different Instagram content formats and educational levels to examine longer-term changes.